IMPLEMENTATION OF EXCELLENT SERVICE TO THE COMMUNITY AT THE KOTANOPAN SUBDISTRICT OFFICE, MANDAILING NATAL REGENCY - Kholilullah; Ritonga, Syafrudin; Batubara, Beby Masitho (Pena Cendekia Insani, 2026)
Excellent service is one of the important pillars in improving the quality of public services that are oriented toward community satisfaction. The Subdistrict Office, as the frontline of government services at the subdistrict level, has a strategic role in meeting community needs in a fast, accurate, and transparent manner. However, in practice, the implementation of services at the subdistrict level still faces various constraints, both those originating from human resources, facilities and infrastructure, and the service system used. This study aims to analyze the implementation of excellent service to the community at the Kotanopan Subdistrict Office, Mandailing Natal Regency, as well as to identify the factors that influence it. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentation. The research informants consisted of the Subdistrict Head, subdistrict officials, and the community as service users. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and drawing meaning. The results of the study indicate that the implementation of excellent service at the Kotanopan Subdistrict Office has been carried out, especially in terms of the attitude of the officers in serving the community. However, the quality of service has not yet been fully optimal, particularly in terms of service facilities, timeliness, and the responsiveness of officers in meeting community needs.